A postura pedagógica do professor alfabetizador e as orientações dos documentos oficiais: o que sustenta uma prática? - Ramos, Iduméa de Souza Fernandes (2019)
The process of literacy that occurs in school does not always achieve the expected success, which causes in the student frustration, delay, difficulties in reading, interpretation and writing. The challenge of the Initial Years is teaching of reading and writing to children under the perspective of literacy, as distinct but interrelated dimensions in the development of reading and writing skills. In this perspecti ve, this work aims to understand the pedagogical posture of the literacy teacher and to describe the approximations or distances between the process of elaboration and application of activities and the guidelines set out in official training documents, from 2009 to 2013. For this, a descriptive and exploratory research was carried out, with a qualitative focus, in which a semi-structured interview, it was used to obtain the data exploratory research for the analysis of the official documents that provide descriptions and guidelines on reading and writing practices in literacy, such as "Pró -Literacy and Language "and the notebooks of the" National Pact for Literacy in the Right Age Training Program "(PNAIC / 2012-2013 – in portuguese). As a basis for the theoretical discussions, the research was based on the studies of Soares (1998, 2017, 2018) to understand the process of literacy and literacy; Freire (2017), Tardif (2014), Nóvoa (2013), Gatti, Perrenoud (2000), among others, to analyze the issues related to emancipatory education, work and teacher knowledge that permeate the pedagogical praxis. To obtain the data were interviewed seven literacy teachers, from a municipal school, located in the South of Minas Gerais . Therefore, the data analysis was constituted from the assumptions of the Grounded Theory (GT). From the data analysis process, categories were constructed to analyze the statements given by the teachers. Three major categories stood out in the process of analysis: 1) training course; 2) conception of reading and literacy; 3) teaching practices. By the categories and analyzes carried out, we sought to identify the methodological conception chosen by the teachers, when performing the classroom activities and, if the teaching action approached or dista nced itself from the guidelines set forth in official continuing education documents. The analyzes revealed that the pedagogical praxis of the literacy teacher is a relevant and significant action, concerned with the formation of the student, as subjects readers, for the exercise of citizenship, however, the theoretical and methodological aspects are still closer to their accumulative experiences than the guidelines contained official training documents.